Hepatic arterial infusion in hepatocellular carcinoma: a single center experience - Melichar, Bohuslav; Dvorak, Josef; Ferko, Alexander; Kamaradova, Katerina; Krajina, Antonin (Biomedical papers, 2015)
Aim: The aim of the present study was to evaluate a single center experience with hepatic arterial infusion (HAI) in patients with hepatocellular carcinoma.Methods: A retrospective analysis of 20 patients treated for hepatocellular carcinoma between 1994 and 2007.Results: Most patients were treated with an HAI of doxorubicin and cisplatin combined with 5-fluorouracil and folinic acid. The response was not evaluable in the majority of patients, predominantly because of associated surgical procedure or because only one cycle of HAI was administered. The median progression-free survival was 7.7 months. The median survival of all patients was 12.2 months (5-year survival 5%). Serious adverse events were observed in 5 patients, and one patient died of liver failure in association with the administration of HAI.Conclusion: The data show the limited efficacy of HAI in patients with hepatocellular carcinoma.
Keywords: hepatic arterial infusion/hepatocellular carcinoma